Embedded Household Specialization: The Bifaces from YāçkEtEl on the Northwest Coast. (3rd October 2022) - Ritchie, Morgan; Morin, Jesse; Ritchie, Jerram; Waber, Nicholas; Blake, Michael; McMillan, Rhy
ABSTRACT: A biface workspace dating to ca. cal a.d. 100–400 was identified during recent excavation at the Sts'ailes-Coast Salish village of YāçkEtEl, on the Harrison River on the Northwest Coast of North America. Based on a range of analyses, we suggest that a specialist crafted large bifaces produced as prestigious objects for exchange within a ceremonial interaction sphere and smaller, more functional bifaces for household and local purposes. The workspace was a shed-like structure adjacent to their house, and the toolstone was acquired nearby from previously undocumented quarries within the territory. This is the only documented evidence for the manufacture of large prestigious bifaces in the region and consequently provides insights into the social relations of lithic acquisition, production, exchange, and consumption. In particular, we examine the social and economic roles and contributions of lithic specialists embedded within households.